Ideal teacher of higher school: Personal qualities and socio-professional competencies - G. Z. Efimova; A. N. Sorokin; M. V. Gribovskiy (Образование и наука)
Introduction. The increasing pace of knowledge renewal around the world and the unification of teacher requirements are changing the functioning and management of the higher education system. Transformational processes in the socio-economic sphere of Russia entail profound changes and increased requirements for the educational process at all its levels. The quality of education is largely determined by teachers, their level of training, the presence of the necessary personal characteristics and social and professional competencies.The aim of the present article is to consider the approaches of Russian and foreign researchers to the classification of competencies of scientific and pedagogical workers, to determine the range of personal qualities and key socio-professional competencies of scientific and pedagogical workers in educational and research activities.Methodology and research methods. Semi-structured expert interviews were conducted with 84 scientific and pedagogical workers of Tyumen State University, Tomsk State University, St. Petersburg Polytechnic University, St. Petersburg University of Information Technologies, Mechanics and Optics. The choice of universities is determined by their participation in the Project 5-100 (Russian Academic Excellence Project) and high positions in Russian university ratings.Results and scientific novelty. A comparative analysis of research approaches allowed the authors to identify an unstructured list of priority competencies (necessary for educational and pedagogical activities) of scientific and pedagogical workers of higher educational institutions. Since educational activities at the university are aimed at the formation of certain professional competencies and values among students, the priority personal qualities and socio-professional competencies in educational activities include the following: highly specialised skills and general erudition; methodological skills; continuing professional development; motivation for pedagogical work; communication skills; emotional intelligence and stress resistance; charisma, modernity in communication; justice; critical thinking and reflection. Pedagogical activity at universities is closely related to the participation of the lecturer in scientific research. The success of pedagogical activity is largely determined by the following aspects: professionalism and desire to update competencies; operability and self-control; teamwork skills; analytical skills and academic writing skills; inclusion in the world scientific agenda; adherence to scientific ethics. The research novelty lies in the compilation of the structured list of personal qualities and socio-professional competencies of a modern teacher in educational and research activities.Practical significance. Using the presented range of significant competencies of scientific and pedagogical workers, HR managers in universities can implement specific management projects aimed at developing personal qualities and social and professional competencies of employees, make informed decisions in the selection and development ofpersonnel, and personnel changes. The research results can also be employed by scientific and pedagogical workers of universities when building their individual trajectories of professional and personal development.